Effect of temperature, humidity and inoculation method on susceptibility of Schistocerca gregaria to Metarhizium flavoride - Fargues, J.; Ouédraogo, A.; Goettel, M.S.; Lomer, C.J. (Informa UK Limited, 1997)
The effects of temperature on conidial germination and susceptibility of adults of the desert locust, Schistocer cagregaria, to four isolates of Meta rhizium flovoviride were determined. In addition, the eff ects of inoculation method (topical or spray), spore carrie r (oil or wat er) and ambient relative humidity (R H ) on susceptibility of the locust to the most thermotolerant isolate (M f324) were investigated. There were differences among the isolates in the effects of temperature on germination of conidia after a 24 -h incubation period. Over 90% of conidia of all isolates germinated after 24 h at 30oC. In contrast, at 40oC, none of the isolates germinated for up to 72 h. However, there were differences in germination between the isolates at 35oC. Locust mortality and disease progression were significantly affected by temperature. At both 25 and 30oC, all isolates induced 98-100% mortality within 8 days; however, there were differences between isolates at 35oC. None of the isolates caused significant mortality at 40oC. Humidity and inoculation method had no influence on levels of mortality in fungus treated locusts. In contrast, carrier type signicantly affected cumulative mortality. Topical oil treatment resulted in higher overall mycosis than the three other treatments. Control mortality on the other hand was strongly affected by inoculation method and to a lesser ex tent by humidity and carrier. In these conditions, application of oil by spray was generally toxic at all humidities whereas topical application of water was most toxic at near saturation. The results of these laboratory studies demonstrate the importance of strain selection, formulation and application method in the development of a microbial control agent against the desert locust .Low R H should not impede use of this fungus under dry conditions.